2017
DOI: 10.5539/jms.v7n1p94
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation and Growth in Mexican Small Business

Abstract: In the literature, there are various studies relating positively the entrepreneurial orientation to business performance. In such studies a great deal of variables have been introduced to measure business performance, among the variables most accepted by researchers and academics are profit and business growth. Therefore, it is possible to consider that entrepreneurial orientation plays an essential role in business growth. For that reason, this paper has the objective to analyse the existing relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…The results indicate that proactiveness has a significant positive relationship with firm performance of SMEs. This finding is consistent with research by Maldonado-Guzman et al (2017), Haider et al (2017), Mojikon et al (2016) who reported that proactiveness has a significant positive impact over firm performance of SMEs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results indicate that proactiveness has a significant positive relationship with firm performance of SMEs. This finding is consistent with research by Maldonado-Guzman et al (2017), Haider et al (2017), Mojikon et al (2016) who reported that proactiveness has a significant positive impact over firm performance of SMEs.…”
Section: Discussionsupporting
confidence: 92%
“…The results interpret that risk-taking propensity has a significant positive relationship with firm performance of SMEs. This finding is matching with the finding by Maldonado-Guzman et al (2017), Haider et al (2017), Gautam (2016), Belgacem (2015) who argued that risk-taking propensity had a significant positive impact over the firm performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Chen and Hambrick (1995) stated that passive and reactive aspects are essential for a firm's growth. Previous studies have shown that proactiveness relates positively to a firm's performance (Haider et al, 2017;Maldonado-Guzman et al, 2017;Yang and Meyer, 2019). Nevertheless, the COVID-19 pandemic may affect that positive relationship as it has disrupted the entire economic ecosystem (Wenzel, 2021).…”
Section: Entrepreneurial Orientation Dimensionproactivenessmentioning
confidence: 99%